IMPROVING THE METHODOLOGY OF MONITORING THE INFORMATION SPACE USING GEOGRAPHIC INFORMATION SYSTEMS - Lukiyanchuk, A.; Storubliov, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
Growing opportunities for the use of modern geographic information technologies in the military sphere force us to reconsider traditional approaches to the use of tools and methods for analyzing existing information and analytical materials to improve the efficiency of information activities in accordance with the competence of the MOU and the Armed Forces. At the same time, the growing intensity of the dynamics of peacetime and armed struggle (conflicts) implies the presence and circulation of a large amount of information that requires processing, storage, transmission to consumers, which makes it impossible for human operator (analyst) to make an informed decision. Under these circumstances, there is a need to use modern geographic information systems aimed at supporting decision-making in conditions of limited, temporal and spatial parameters. Changes in the content of passive intelligence are associated with the use of geographic information systems (GIS), which combine the collection, processing of information about the area with hydrometeorological, operational and tactical, intelligence and other information, which provides qualitative analysis and modeling of the most rational solutions. in the interests of armed struggle. The constant increase in the amount of information required and the reduction of decision-making time determine the urgency of the problem, to solve which it is necessary to develop geographic information systems and use them in planning and managing combat operations of units of the Armed Forces of Ukraine. One of the tasks of passive remote reconnaissance is to identify the coordinates of the enemy. In the future, these coordinates must be presented in a user-friendly form. This is achieved through the creation of military information systems for various purposes, an important component of which are the means of processing digital information about the area in conjunction with various data about the enemy and their troops. It is possible to solve such problems with the use of passive remote reconnaissance systems based on reconnaissance and signaling devices. Based on the analysis of existing RSPs for the effective solution of such problems, one of the possible options is the use of seismic acoustic systems. The operation of seismic systems is based on the detection of the presence in the environment of propagation (surface layer of the earth) of seismic waves that occur during the movement of the intruder in the observation area using seismic sensors and (air, liquids or solids) acoustic waves using acoustic sensors. The use of passive remote reconnaissance based on seismic monitoring together with geographic information systems will eliminate the human factor (errors), reduce human costs, reduce time costs for data processing, and store the information in GIS databases, which is relevant to this topic. The use of geographic information systems will eliminate personnel losses.